A preparation method for increasing the pore structure of metal-based hollow fiber tube wall by template etching method

The preparation of metal-based hollow fibers through template etching method solves the problem of insufficient control of the pore structure in the prior art, and realizes the regulation of the gas mass transfer speed and the improvement of reaction efficiency. It is suitable for electrocatalytic energy storage and conversion applications.

CN117328167BActive Publication Date: 2024-12-27LINYI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311267693.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2024-12-27
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

The prior art cannot effectively control the wall channel structure of metal-based hollow fiber tubes, limits the gas mass transfer speed and reaction efficiency, and affects the application of electrocatalytic energy storage and conversion.

Method used

Metal-based hollow fibers are prepared by template etching. By mixing template powder, metal or metal oxide powder with molding agent and organic solvent, calcining in a reducing atmosphere and selective etching, the channel structure is accurately controlled. .

Benefits of technology

It realizes precise control of the hole structure of metal-based hollow fiber tube walls, adjusts the gas mass transfer speed, improves reaction activity and stability, broadens the application range, and is characterized by simple operation and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004474680960000011
    Figure HDA0004474680960000011
  • Figure HDA0004474680960000012
    Figure HDA0004474680960000012
  • Figure HDA0004474680960000013
    Figure HDA0004474680960000013
Patent Text Reader

Abstract

The present invention discloses a preparation method for increasing the pore structure of the metal-based hollow fiber tube wall by a template etching method, belonging to the field of new electrochemical materials. The steps are as follows: (1) mixing template powder, metal or metal oxide powder, forming agent and organic solvent to obtain spinning solution; (2) extruding the spinning solution through a coaxial needle outer shaft, and obtaining hollow filaments through a shaping process; (3) calcining the hollow filaments in air or oxygen to obtain metal oxide-based hollow fibers; (4) calcining and reducing in a reducing atmosphere; (5) removing the template particles through a selective etching step to obtain metal-based hollow fibers with rich pores and adjustable pore size. The template etching method does not affect the self-supporting structure of the hollow fiber, and the obtained metal-based hollow fiber tube wall has an adjustable pore structure, so it can effectively adjust the internal and external transmission of gas, which has a breakthrough significance for the application of metal-based hollow fibers in gas-fed electrocatalytic energy storage and conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of new electrochemical materials, and in particular relates to a preparation method for increasing the pore structure of a metal-based hollow fiber tube wall by a template etching method. Background Art

[0002] The increase in the world's population and the rapid development of society have led to a sharp increase in the consumption of traditional fossil fuels, causing obvious energy shortages and environmental pollution problems. The world's demand for renewable energy is becoming more and more urgent. Governments of various countries have introduced policies to strongly support the development and utilization of sustainable new energy. Among them, renewable energy (wind, hydro, tidal, geothermal, etc.) power generation shows the potential to replace traditional fossil energy and help alleviate the energy and environmental crisis. However, renewable energy has inherent characteristics such as intermittent and random. Therefore, the development and use of new energy storage and conversion devices for electricity plays a very critical role in the full utilization and efficient conversion of renewable electricity. Electrocatalytic energy storage and conversion devices, such as fuel cells and water electrolysis devices, are already in the early stage of large-scale industrialization, which fully demonstrates the great value and potential of electrochemical devices in energy storage and conversion, and will help achieve the dual carbon strategy.

[0003] In recent years, researchers have found that driven by renewable energy electricity, small molecules such as carbon dioxide, nitrogen, and water can be converted into fuels and chemicals such as methanol, formic acid, ethylene, ammonia, and hydrogen through electrolyzer devices, while achieving customized synthesis of compounds and effective storage of electrical energy. As an efficient and clean energy conversion device, the electrolyzer device has the advantages of simple operation, mild conditions, and environmental friendliness. The efficient operation of such electrochemical devices is based on the electrochemical catalytic process occurring at the anode and cathode. The overall performance of the device depends to a large extent on the electrocatalytic materials at the anode and cathode. Therefore, the development of efficient new electrocatalytic materials is a key factor and challenging issue in promoting the industrial application of such electrochemical devices.

[0004] Many of the electrochemical catalytic processes occurring at the anode and cathode are gas feed reactions, and the mass transfer problem of the reaction gas limits the rate and progress of the reaction. The use of a gas diffusion electrode structure can solve the problem of limited mass transfer, but the current gas diffusion layer usually uses hydrophobic carbon paper. The hydrophobicity of the electrolyzer assembled with this catalyst-loaded carbon paper as an electrode will gradually weaken under high current density operating conditions, causing problems such as flooding and salt precipitation, resulting in the operating stability of the electrolyzer device failing to meet application requirements, which seriously affects the industrial application process of this technical solution.

[0005] Metal-based hollow fiber electrodes are a new type of electrode. On the one hand, they retain the mass transfer advantages of traditional gas diffusion layer electrodes in terms of function; on the other hand, the inherent rigid electrode structure has a forced mass transfer function from the inside to the outside, and the surface catalyst layer directly contacts the electrolyte, which can effectively avoid the flooding and salt precipitation problems faced by traditional gas diffusion layer electrodes. Therefore, metal-based hollow fiber electrodes have obvious structural and performance advantages under high current density operating conditions, and their core elements lie in the self-supporting structure and the pore structure of the tube wall.

[0006] The Chinese patent with publication number CN114395777A introduces a metal self-supporting electrode, preparation method and application. A series of metal tubes with different components are obtained by dry-wet spinning, which have good catalytic performance in carbon dioxide reduction, nitrogen reduction, glycerol oxidation, methane oxidation and other reactions. The method has the characteristics of simple process, low cost and industrialization suitable for mass production.

[0007] However, the current technical solutions cannot control the pore structure of the tube wall, and therefore have great limitations in controlling gas mass transfer. An effective method for controlling the pore structure needs to be developed. Summary of the invention

[0008] The technical task of the present invention is to solve the deficiency of the prior art that the pore size of the metal tube wall cannot be controlled. The purpose is to provide a new preparation method, which can accurately control the pore size of the metal-based hollow fiber wall without affecting the self-supporting structure of the hollow fiber, thereby effectively regulating the mass transfer rate of the gas. It has a breakthrough significance for the application of metal-based hollow fibers in electrocatalytic energy storage and conversion of gas feed.

[0009] In order to achieve the above-mentioned object and other related objects, the present invention provides a preparation method for increasing the pore structure of the metal-based hollow fiber tube wall by a template etching method, the preparation method comprising:

[0010] S1, mixing template powder, metal or metal oxide powder, a forming agent and an organic solvent to obtain a spinning solution;

[0011] S2, the spinning solution is uniformly extruded through the outer shaft of the coaxial needle under the push of the injection pump, and undergoes a shaping process to obtain a hollow precursor;

[0012] S3, calcining the hollow filament in air or oxygen to obtain a metal oxide-based hollow fiber;

[0013] S4, calcining and reducing the metal oxide-based hollow fiber in a reducing atmosphere to obtain a reduced metal-based hollow fiber;

[0014] S5, the reduced metal-based hollow fiber is subjected to a selective etching step to remove the template, thereby obtaining a metal-based hollow fiber with abundant pores and adjustable pore size.

[0015] Preferably, the template powder in S1 includes one or a combination of two or more of zinc oxide powder and silicon oxide powder.

[0016] Preferably, the metal powder in S1 includes one or a combination of two or more of titanium powder, iron powder, cobalt powder, nickel powder, copper powder, silver powder, bismuth powder and tin powder.

[0017] Preferably, the metal oxide powder in S1 includes one or a combination of two or more of titanium oxide powder, iron oxide powder, cobalt oxide powder, nickel oxide powder, copper oxide powder, silver oxide powder, bismuth oxide powder and tin oxide powder.

[0018] Preferably, in S1, the molding agent includes one or a combination of two or more of polyvinyl pyrrolidone, polyacrylonitrile, polyetherimide, polyethylene, polypropylene, polyvinyl alcohol, and polymethyl methacrylate.

[0019] Preferably, the solvent in S1 includes one or a combination of two or more of ethanol, methanol, N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide.

[0020] Preferably, in S1, the template powder, metal or metal oxide powder has a particle size of 10 nm to 100 μm.

[0021] Preferably, in the spinning solution described in S1, in terms of mass percentage, the template powder accounts for 5wt% to 25wt%, the metal or metal oxide powder accounts for 10wt% to 50wt%, the molding agent accounts for 5wt% to 30wt%, and the organic solvent accounts for 10wt% to 60wt%.

[0022] Preferably, the mixing method in S1 is one or a combination of stirring, grinding and ball milling, and the duration is 1 to 48 hours.

[0023] Preferably, the shaping process in S2 is dry spinning or dry-wet spinning.

[0024] Preferably, in S3, the calcination temperature is 300-1000°C, the initial temperature is room temperature, and the heating and cooling rate is 1-20°C / min.

[0025] Preferably, in S4, the calcination temperature is 300-1500° C., the initial temperature is room temperature, and the heating and cooling rate is 1-20° C. / min; the reducing atmosphere is a circulating hydrogen-argon atmosphere with a flow rate of 10-500 mL / min.

[0026] Preferably, in S5, the etching step is one or a combination of high-temperature reduction evaporation or etching with an etching liquid; the high-temperature reduction evaporation is high-temperature calcination in a reducing atmosphere; the etching liquid is one or a combination of two or more of hydrochloric acid, nitric acid, sulfuric acid, hydrofluoric acid, oxalic acid, sodium hydroxide, potassium hydroxide, ammonia water, and ammonium fluoride, and the etching time is 1 to 48 hours.

[0027] Preferably, the outer diameter of the metal-based hollow fiber is 300 μm to 2 mm, the wall thickness is 10 μm to 300 μm, and the pore size is 100 nm to 100 μm.

[0028] The metal-based hollow fiber is used as an electrode for electrocatalytic reactions of gas feeds, including but not limited to oxygen reduction reaction, carbon dioxide reduction reaction, nitrogen reduction reaction, acetylene reduction reaction, methane oxidation reaction, ethylene oxidation reaction, etc.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] (1) This template etching method can accurately control the pore structure size of the tube wall without affecting the self-supporting structure of the hollow fiber, effectively adjust the gas mass transfer rate, and is conducive to broadening the application range of metal-based hollow fibers.

[0031] (2) This method uses a highly selective etching template based on the different boiling points of different component materials under high-temperature reducing conditions or the difference in solubility in the etching solution to obtain a size-controllable pore structure with reasonable design and strong operability.

[0032] (3) Metal-based hollow fibers with controllable pore structures can effectively accelerate mass transfer, improve reaction activity, reaction rate and stability, and have groundbreaking significance in the application of electrocatalytic energy storage and conversion of gas feeds.

[0033] (4) The preparation method is simple to operate, highly controllable, and has good repeatability; the selected template materials are abundant in raw materials and low in cost, and have great value for promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a scanning electron microscope (SEM) image of the zinc oxide template used in Example 1 of the present invention;

[0035] Figure 2 This is a scanning electron microscope (SEM) image of the zinc oxide-copper oxide-based hollow fiber prepared in Example 1;

[0036] Figure 3 This is a scanning electron microscope (SEM) image of the porous copper-based hollow fiber prepared in Example 1;

[0037] Figure 4 This is a scanning electron microscope (SEM) image of the copper-based hollow fiber prepared in Comparative Example 1. DETAILED DESCRIPTION

[0038] The present invention is further explained below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. After reading the present invention, various equivalent modifications to the present invention by those skilled in the art all fall within the scope of protection of the claims of this application.

[0039] Example 1

[0040] (1) A zinc oxide template (particle size 10 μm), copper powder (particle size 1 μm), polyetherimide and N-methylpyrrolidone were ground and mixed in a mass ratio of 20%, 20%, 20% and 40%, respectively, and stirred for 48 hours to obtain a spinning solution;

[0041] (2) The spinning solution is extruded through the outer shaft of the coaxial needle by a propulsion pump at a speed of 10 mm / min, through the air layer, and into the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is N-methylpyrrolidone, the flow rate is 15 mm / min, and the coagulation liquid is distilled water;

[0042] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by dry spinning to obtain a hollow raw fiber;

[0043] (4) calcining the hollow filaments in an air atmosphere, starting from room temperature, raising the temperature to 600° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain zinc oxide-copper oxide-based hollow fibers;

[0044] (5) calcining and reducing the zinc oxide-copper oxide-based hollow fiber in a circulating hydrogen-argon atmosphere (50 mL / min), starting from room temperature, raising the temperature to 800° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-copper oxide-based hollow fiber;

[0045] (6) The zinc oxide-copper-based hollow fiber is placed in a dilute hydrochloric acid (1 M) etching solution and etched for 3 h to selectively remove the zinc oxide template. After washing and drying, a copper-based hollow fiber with rich pores and controllable pore size is obtained.

[0046] Scanning electron microscopy showed that the outer diameter of the copper-based hollow fiber was 0.9-1 mm, the wall thickness was 100-200 μm, the pores were abundant, and the pore size was 5-15 μm.

[0047] Example 2

[0048] (1) mixing a silica template (particle size 200 nm), silver powder (particle size 800 nm), polyetherimide and N-methylpyrrolidone in a weight ratio of 15%, 30%, 15% and 40%, respectively, and stirring for 48 hours to obtain a spinning solution;

[0049] (2) Extruding the spinning solution through the outer shaft of the coaxial needle through a propulsion pump at a speed of 10 mm / min, passing through the air layer, and entering the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is distilled water, the flow rate is 10 mm / min, and the coagulation liquid is distilled water;

[0050] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by dry spinning to obtain a hollow raw fiber;

[0051] (4) calcining the hollow fiber in an air atmosphere, starting from room temperature, raising the temperature to 600° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a silicon oxide-silver oxide-based hollow fiber;

[0052] (5) calcining and reducing the silica-silver oxide-based hollow fiber in a circulating hydrogen-argon atmosphere (50 mL / min), starting from room temperature, raising the temperature to 500° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a silica-silver oxide-based hollow fiber;

[0053] (6) The silica-silver-based hollow fiber was placed in a sodium hydroxide (4M, 80°C) etching solution and etched for 12 h to selectively remove the silica template. After washing and drying, a silver-based hollow fiber with rich pores and controllable pore size was obtained.

[0054] Scanning electron microscopy revealed that the outer diameter of the silver-based hollow fiber was 300-500 μm, the wall thickness was 10-50 μm, the pores were abundant, and the pore size was 150 nm-250 nm.

[0055] Example 3

[0056] (1) zinc oxide template (particle size 50 μm), copper powder (particle size 100 μm), cobalt powder (particle size 100 μm), nickel powder (particle size 100 μm), polyvinyl alcohol and N,N-dimethylformamide were mixed uniformly by ball milling at mass ratios of 25%, 3%, 3%, 4%, 30% and 35%, respectively, and stirred for 48 hours to obtain a spinning solution;

[0057] (2) The spinning solution is extruded through the outer shaft of the coaxial needle by a propulsion pump at a speed of 10 mm / min, through the air layer, and into the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is distilled water, the flow rate is 15 mm / min, and the coagulation liquid is distilled water;

[0058] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by a dry-wet spinning process to obtain a hollow raw fiber;

[0059] (4) calcining the hollow fiber in an air atmosphere, starting from room temperature, raising the temperature to 1000° C. at a rate of 20° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-composite oxide metal-based hollow fiber;

[0060] (5) calcining and reducing the zinc oxide-composite metal oxide-based hollow fiber in a circulating hydrogen-argon atmosphere (50 mL / min), starting from room temperature, heating to 500° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-composite metal-based hollow fiber;

[0061] (6) The zinc oxide-composite metal-based hollow fiber is placed in a dilute sulfuric acid (1 M) etching solution and etched for 48 hours to selectively remove the zinc oxide template. After washing and drying, a composite metal-based hollow fiber with rich pores and controllable pore size is obtained.

[0062] Scanning electron microscopy showed that the outer diameter of the copper-cobalt-nickel composite metal-based hollow fiber was 1.8-2 mm, the wall thickness was 250-300 μm, the pores were abundant, and the pore size was 30-70 μm.

[0063] Example 4

[0064] (1) grinding and mixing a silica template (particle size 50 μm), tin powder (particle size 50 μm), polymethyl methacrylate and dimethyl sulfoxide in a mass ratio of 5%, 50%, 5% and 40%, respectively, and stirring for 48 hours to obtain a spinning solution;

[0065] (2) The spinning solution is extruded through the outer shaft of the coaxial needle by a propulsion pump at a speed of 10 mm / min, through the air layer, and into the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is distilled water, the flow rate is 15 mm / min, and the coagulation liquid is distilled water;

[0066] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by dry spinning to obtain a hollow raw fiber;

[0067] (4) calcining the hollow fiber in an air atmosphere, starting from room temperature, raising the temperature to 500° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a silicon oxide-tin oxide-based hollow fiber;

[0068] (5) calcining and reducing the silicon oxide-tin oxide-based hollow fiber in a circulating hydrogen and argon atmosphere (50 mL / min), starting from room temperature, raising the temperature to 1500° C. at a rate of 20° C. / min, and keeping the temperature for 3 h to obtain a silicon oxide-tin-based hollow fiber;

[0069] (6) The silicon oxide-tin-based hollow fiber was placed in a potassium hydroxide (4M, 80°C) etching solution and etched for 36 hours to selectively remove the silicon oxide template. After washing and drying, a tin-based hollow fiber with rich pores and controllable pore size was obtained.

[0070] Scanning electron microscopy showed that the outer diameter of the tin-based hollow fiber was 1.5-1.6 mm, the wall thickness was 280-300 μm, the pores were abundant, and the pore size was 40-60 μm.

[0071] Example 5

[0072] (1) Grinding and mixing zinc oxide template (particle size 10 μm), titanium powder (particle size 10 μm), polyvinyl pyrrolidone and methanol in mass proportions of 25%, 10%, 5% and 60%, respectively, and stirring for 48 hours to obtain a spinning solution;

[0073] (2) The spinning solution is extruded through the outer shaft of the coaxial needle by a propulsion pump at a speed of 10 mm / min, through the air layer, and into the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is methanol, the flow rate is 15 mm / min, and the coagulation liquid is distilled water;

[0074] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by dry spinning to obtain a hollow raw fiber;

[0075] (4) calcining the hollow filament in an air atmosphere, starting from room temperature, raising the temperature to 800° C. at a rate of 10° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-titanium oxide-based hollow fiber;

[0076] (5) calcining and reducing the zinc oxide-titanium oxide-based hollow fiber in a circulating hydrogen-argon atmosphere (50 mL / min), starting from room temperature, heating to 1500° C. at a rate of 10° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-titanium-based hollow fiber;

[0077] (6) The zinc oxide-titanium-based hollow fiber was placed in a dilute nitric acid (1 M) etching solution and etched for 20 h to selectively remove the zinc oxide template. After washing and drying, a titanium-based hollow fiber with abundant pores and controllable pore size was obtained.

[0078] Scanning electron microscopy showed that the outer diameter of the titanium-based hollow fiber was 1.2-1.3 mm, the wall thickness was 90-100 μm, the pores were abundant, and the pore size was 5-15 μm.

[0079] Example 6

[0080] (1) Grinding and mixing zinc oxide template (particle size 1 μm), copper oxide powder (particle size 1 μm), polyacrylonitrile and N,N-dimethylformamide in a mass ratio of 10%, 50%, 30% and 10%, respectively, and stirring for 48 hours to obtain a spinning solution;

[0081] (2) The spinning solution is extruded through the outer shaft of the coaxial needle by a propulsion pump at a speed of 10 mm / min, through the air layer, and into the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is ethanol, the flow rate is 15 mm / min, and the coagulation liquid is distilled water;

[0082] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by dry spinning to obtain a hollow raw fiber;

[0083] (4) calcining the hollow fiber in an air atmosphere, starting from room temperature, raising the temperature to 600° C. at a rate of 5° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-copper oxide-based hollow fiber;

[0084] (5) calcining and reducing the zinc oxide-copper oxide-based hollow fiber in a circulating hydrogen-argon atmosphere (50 mL / min), starting from room temperature, raising the temperature to 800° C. at a rate of 5° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-copper oxide-based hollow fiber;

[0085] (6) The zinc oxide-copper-based hollow fiber is placed in a dilute hydrochloric acid (1 M) etching solution and etched for 1 h to selectively remove the zinc oxide template. After washing and drying, a copper-based hollow fiber with rich pores and controllable pore size is obtained.

[0086] Scanning electron microscopy showed that the outer diameter of the copper-based hollow fiber was 0.8-1 mm, the wall thickness was 150-200 μm, the pores were abundant, and the pore size was 0.5-1.5 μm.

[0087] Example 7

[0088] (1) grinding and mixing zinc oxide template (particle size 500 nm), silver oxide powder (particle size 500 nm), polyetherimide and N-methylpyrrolidone in weight ratios of 20%, 20%, 20% and 40%, respectively, and stirring for 48 hours to obtain a spinning solution;

[0089] (2) The spinning solution is extruded through the outer shaft of the coaxial needle by a propulsion pump at a speed of 10 mm / min, through the air layer, and into the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is N-methylpyrrolidone, the flow rate is 15 mm / min, and the coagulation liquid is distilled water;

[0090] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by dry spinning to obtain a hollow raw fiber;

[0091] (4) calcining the hollow filament in an air atmosphere, starting from room temperature, raising the temperature to 600° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-silver oxide-based hollow fiber;

[0092] (5) calcining and reducing the zinc oxide-silver oxide-based hollow fiber in a circulating hydrogen-argon atmosphere (50 mL / min), starting from room temperature, heating to 800° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-silver-based hollow fiber;

[0093] (6) The zinc oxide-silver-based hollow fiber was placed in a dilute hydrochloric acid (1 M) etching solution and etched for 3 h to selectively remove the zinc oxide template. After washing and drying, a silver-based hollow fiber with rich pores and controllable pore size was obtained.

[0094] Scanning electron microscopy showed that the outer diameter of the silver-based hollow fiber was 1.1-1.2 mm, the wall thickness was 250-300 μm, the pores were abundant, and the pore size was 400-600 nm.

[0095] Example 8

[0096] (1) Grinding and mixing zinc oxide template (particle size 200 nm), titanium oxide powder (particle size 50 nm), polypropylene and N-methylpyrrolidone in a mass ratio of 20%, 20%, 20% and 40%, respectively, and stirring for 48 hours to obtain a spinning solution;

[0097] (2) The spinning solution is extruded through the outer shaft of the coaxial needle by a propulsion pump at a speed of 10 mm / min, through the air layer, and into the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is N-methylpyrrolidone, the flow rate is 15 mm / min, and the coagulation liquid is distilled water;

[0098] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by dry spinning to obtain a hollow raw fiber;

[0099] (4) calcining the hollow fiber in an air atmosphere, starting from room temperature, raising the temperature to 600° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-titanium oxide-based hollow fiber;

[0100] (5) calcining and reducing the zinc oxide-titanium oxide-based hollow fiber in a circulating hydrogen-argon atmosphere (50 mL / min), starting from room temperature, raising the temperature to 1400° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a zinc oxide-titanium-based hollow fiber;

[0101] (6) The zinc oxide-titanium-based hollow fiber was placed in a dilute hydrochloric acid (1 M) etching solution and etched for 3 h to selectively remove the zinc oxide template. After washing and drying, a titanium-based hollow fiber with abundant pores and controllable pore size was obtained.

[0102] Scanning electron microscopy revealed that the outer diameter of the titanium-based hollow fiber was 600-700 μm, the wall thickness was 30-40 μm, the pores were abundant, and the pore size was 150-250 nm.

[0103] Comparative Example 1

[0104] (1) copper powder (particle size 1 μm), polyetherimide and N-methylpyrrolidone were ground and mixed in a mass ratio of 40%, 20% and 40%, respectively, and stirred for 48 hours to obtain a spinning solution;

[0105] (2) The spinning solution is extruded through the outer shaft of the coaxial needle by a propulsion pump at a speed of 10 mm / min, through the air layer, and into the coagulation liquid to obtain a metal-polymer composite fiber with a hollow structure; the liquid used in the inner shaft is N-methylpyrrolidone, the flow rate is 15 mm / min, and the coagulation liquid is distilled water;

[0106] (3) washing, drying, and shaping the hollow metal-polymer composite fiber by dry spinning to obtain a hollow raw fiber;

[0107] (4) calcining the hollow filaments in an air atmosphere, starting from room temperature, raising the temperature to 600° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain zinc oxide-copper oxide-based hollow fibers;

[0108] (5) calcining and reducing the copper oxide-based hollow fiber in a circulating hydrogen and argon atmosphere (50 mL / min), starting from room temperature, heating to 800° C. at a rate of 1° C. / min, and keeping the temperature for 3 h to obtain a copper-based hollow fiber;

[0109] (6) The metal-based hollow fiber is placed in a dilute hydrochloric acid (1 M) etching solution and etched for 3 h. After washing and drying, a copper-based hollow fiber is obtained.

[0110] The difference between Comparative Example 1 and Example 1 is that no zinc oxide template is used in Comparative Example 1. Figure 4 ) It can be observed that its pore structure is significantly less than that of the copper-based hollow fiber obtained in Example 1 ( Figure 3 ). It can be seen that the pore structure of the metal-based hollow fiber prepared by conventional dry-wet spinning is significantly less than that of the metal-based hollow fiber prepared by the above-mentioned template etching method. The controllability of the pore structure of the metal-based hollow fiber obtained by the present invention greatly exceeds that of the conventional method.

Claims

1. A method for preparing a metal-based hollow fiber tube wall pore structure by a template etching method, comprising the following steps: S1, mixing a template powder, a metal powder or a metal oxide powder, a molding agent and an organic solvent to obtain a spinning solution; the template powder is zinc oxide powder; the metal powder is one of copper powder and silver powder; the metal oxide powder is one of copper oxide powder and silver oxide powder; the molding agent is one of polyacrylonitrile, polyetherimide and polymethyl methacrylate or a combination of two of them; the organic solvent is one of ethanol, methanol, N,N-dimethylformamide and N-methylpyrrolidone or a combination of two or more of them; S2, the spinning solution is uniformly extruded through the outer shaft of the coaxial needle under the push of the injection pump, and undergoes a shaping process to obtain a hollow precursor; S3, calcining the hollow filament in air or oxygen to obtain a metal oxide-based hollow fiber; S4, the metal oxide-based hollow fiber is calcined and reduced in a reducing atmosphere to obtain a reduced metal-based hollow fiber; the calcination temperature is 300-1500°C, the initial temperature is room temperature, and the heating and cooling rate is 1-20°C / min; the reducing atmosphere is a circulating hydrogen-argon atmosphere with a flow rate of 10-500 mL / min; S5, the reduced metal-based hollow fiber is subjected to a selective etching step to remove the template particles to obtain a metal-based hollow fiber with abundant pores and adjustable pore size; the etching step is etching with an etching solution; the etching solution used in the etching with the etching solution is hydrochloric acid; the etching time of the etching step is 1 to 48 h; the outer diameter of the prepared metal-based hollow fiber is 300 μm to 2 mm, the wall thickness is 10 μm to 300 μm, and the pore size is 100 nm to 100 μm.

2. The preparation method according to claim 1, characterized in that The particle size of the template powder, metal powder or metal oxide powder in S1 is 10 nm~100 μm; in the spinning solution, the mass percentage of the template powder is 5 wt%~25wt%, the mass percentage of the metal powder or metal oxide powder is 10 wt%~50 wt%, the mass percentage of the forming agent is 5 wt%~30 wt%, and the mass percentage of the organic solvent is 10 wt%~60 wt%; the mixing method is one or a combination of two or more of stirring, grinding and ball milling, and the duration is 1~48 h.

3. The preparation method according to claim 1, characterized in that: The shaping process described in S2 is dry spinning or dry-wet spinning.

4. The preparation method according to claim 1, characterized in that: The calcination temperature in S3 is 300-1000°C, the initial temperature is room temperature, and the heating and cooling rate is 1-20°C / min.

5. Use of a metal-based hollow fiber prepared by the preparation method according to any one of claims 1 to 4 in an electrocatalytic reaction, characterized in that: The metal-based hollow fiber is used as an electrode for the electrocatalytic reaction of gas feed; the electrocatalytic reaction is oxygen reduction reaction, carbon dioxide reduction reaction, nitrogen reduction reaction, acetylene reduction reaction, methane oxidation reaction or ethylene oxidation reaction.